Endogenous capital-augmenting technological change - Gregory Casey; Ryo Horii (Osaka University, Institute of Social and Economic Research (ISER), 2023)
We construct a 3-factor, directed technical change growth model that ex-hibits capital-augmenting technical change on the balanced growth path (BGP), circumventing the issues usually caused by the 2-factor Uzawa growth theorem. We calibrate the model to the United States and consider a non-unitary elasticity of substitution between capital and labor. We show that the model converges to the BGP with capital-augmenting technical change from any initial condition. Our results indicate that natural resources and directed technical change play a central role in explaining balanced growth.
Keywords: E13; E22; O33; O41; 330; Balanced Growth; Uzawa Steady-State Growth Theorem; Directed Technical Change (DTC); Natural Resources; Three-Factor Model